Pesništvo kot mimesis v Aristotelovi Poetiki - Marušič, Jera (Primerjalna književnost, 2009)
In the opening of the Poetics, Aristotle suggests that mimesis, rather than verse, is the defining feature of poetry. This article aims to shows both the vagueness and the implausibility of this basic claim of Aristotle's account of poetry.
Keywords: Plato, 427-347 pr. n. št.; Aristoteles, 384-322 pr. n. št.; antična estetika; poetika; mimesis